The Role of Organizational Commitment and Innovation In Mediating The Influence of Visionary Leadership and Competence on Employee Performance - Marlita, Livia; Budiyanto, Budiyanto; Agustedi, Agustedi (Devotion : Journal of Research and Community Service, 2024)
This study explores the impact of visionary leadership and competence on employee performance, with a focus on the mediating roles of organizational commitment and innovation. Conducted within the context of civil servants in Pekanbaru City, this research employs a quantitative approach to investigate the relationships between these variables. The results reveal that visionary leadership has a significant positive effect on employee performance, both directly and through the mediating role of organizational commitment. Competence also significantly influences employee performance, but this effect is primarily channeled through innovation, which acts as a key mediator. The findings underscore the importance of fostering visionary leadership and enhancing competence to boost organizational commitment and innovation, ultimately leading to improved employee performance. This study contributes valuable insights into the mechanisms by which leadership and competence can be leveraged to achieve higher levels of performance in public sector organizations. Practical implications include strategies for developing leadership and competence to enhance the productivity and effectiveness of civil servants.